A Deep‐Red to Near Infrared (NIR) Fluorescent Probe Based on a Sulfur‐Modified Rhodamine Derivative with Two Spirolactone Rings. Issue 8 (4th August 2020) - Tian, Xinyu; Liu, Huawei; Wei, Fangfang; Wang, Xiangchuan; Zhao, Shunan; Liu, Chuangjun; Tse, Yu Chung; Wong, Keith Man‐Chung
Abstract: We report the synthesis, characterization, and photophysical and ion‐binding properties of deep‐red to near‐infrared (NIR) fluorescent rhodamine derivatives, bearing two spirolactone rings and substitution of the oxygen atoms in the xanthene ring with sulfur atoms (1‐S ). The diastereoisomeric cis ‐ and trans ‐forms of the rhodamine derivative were separated and the cis ‐form ( cis ‐1‐S ) was structurally characterized by X‐ray crystallography. Upon treatment with Hg 2+ ion, cis ‐1‐S was converted into the dual spirolactone ring‐opened species, resulting in significant color change and fluorescence enhancement. Substitution of the oxygen atoms with sulfur and extended π‐conjugation across the fused six‐membered rings upon the two rings‐opening processes in the presence of Hg 2+ ion led to a significant red‐shift of absorption (623 nm) and fluorescence (706 nm) peaks, compared to the ordinary rhodamine. Furthermore, the intracellular Hg 2+ ‐sensing properties of the cis ‐1‐S have been studied by confocal microscopy. Abstract : Two is better than one : A sulfur‐modified rhodamine derivative with two spirolactone rings undergoes successive ring‐opening reactions with drastic color changes and fluorescence enhancement in the presence of Hg 2+ ions. The replacement of oxygen atoms with sulfur atoms in the xanthene moiety was demonstrated to induce a significant red shift in the absorption and fluorescence, thus allowing the development of a deep‐red to NIR fluorescent probe.